Integrasi Sistem Transportasi sebagai Daya Dukung Pertumbuhan Ekonomi di Aceh - Jufridar, Jufridar; Saifuddin, Saifuddin (Jurnal Sosiologi Dialektika Sosial, 2023)
This article discusses the integration of the transportation system as a support for economic growth in Aceh. Through observations, interviews and document data, this article questions how the integration of the transportation system in Aceh can support the community's economic growth. The result that can be formulated is that the biggest challenge to the integration of the transportation system in Aceh is closely related to infrastructure and people's behavior in the transportation system. This is also related to all aspects of the ideal transportation infrastructure development so that distribution channels and public access can be guaranteed and maintainedArtikel ini membahas tentang integrasi sistem transportasi sebagai daya dukung pertumbuhan ekonomi di Aceh. Melalui observasi, wawancara dan data dokumen, artikel ini mempertanyakan bagaimana integrasi sistem transportasi di Aceh yang dapat memberi daya dukung pertumbuhan ekonomi masyarakat. Hasil yang dapat dirumuskan adalah tantangan terbesar integrasi sistem trasportasi di Aceh berkaitan erat dengan inflastruktur dan perilaku masyarakat sistem transportasi. Hal ini juga berkaitan dengan segala lini aspek pembangunan inflastruktur trasportasi yang ideal sehingga jalur distribusi dan akses masyarakat dapat terjamin dan terjaga.